THE DECONSTRUCTION OF JEJER GANDRUNG STAGE IN THE VERSE OF GANDRUNG TEROB SONG BANYUWANGI - Robby Cahyadi (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2022)
The interactive cultural discourse in the Gandrung Terob song verses can provide a new indication. The song verse applied in the Gandrung Terob are an oral presentation and surely have their own purpose and meaning in it. The verse of the song contains a presentation of the original language of the City of Banyuwangi,, namely: Osing language used by indigenous people in Kemiren village. This study examines the use of the Gandrung Terob song verses in the first stage of Jejer Gandrung. The purpose of this study is to describe how the function of the Gandrung Terob song verse in the City of Banyuwangi. This study uses a qualitative approach with a descriptive type of research. The data in this study are in the form of song verse speech used during the Jejer Gandrung staging in the Gandrung Terob performance. The scalpel used by researchers uses analysis in terms of cultural discourse. Meanwhile, on the data of the reading the verses of the Gandrung Terob song, the researcher transcribed the verses of the song using heuristic and hermeneutic reading techniques as reference. In addition, the main data analysis technique reference, the researcher using John W. Creswell's data analysis technique. Thus, the data obtained will be more valid and clear. The source of the data in the study was obtained from the speech contained in the Jejer Gandrung stage of the Gandrung Terob song verses in the City of Banyuwangi. The results of this study found 329 data consisting of three sub-focuses contained in the formulation of the problem. Hopefully this research can be used as an additional reference in the study of cultural discourse analysis.